Мистецька освіта у початковій школі Євросоюзу: тенденції розвитку - Олена Ярова (Pavlo Tychyna Uman State Pedagogical University, 2014)
Статтю присвячено висвітленню проблеми становлення суспільства знань та особливостям модернізації європейської системи вищої освіти. В статті розглянуто концепції та характеристики суспільств, які передували становленню суспільства знань, обґрунтовано необхідність суспільних змін, визначено характерні риси суспільства знань та передумови його виникнення. Схарактеризовано роль та завдання освіти в суспільстві знань. Викладено концепції провідних науковців стосовно досліджуваної проблеми та окреслено пріоритетні напрямки розвитку суспільства знань. В статье рассмотрены национальные особенности организации художественного образования на уровне МСКО 1 в странах Европейского Союза. Проанализированы ключевые политические события и инициативы начала XXI века в области образования и культуры со стороны ЕС. Отдельное внимание уделяется целям художественного образования, его содержанию, статусу, моделям обучения. Охарактеризованы подходы к оцениванию учебных достижений младших школьников в данной сфере, проблемы профессиональной подготовки и поддержки учителей начальной школы. Определены общие тенденции развития художественного образования в начальной школе Евросоюза. The article describes the peculiarities of arts education organization at ISCED 1 in the European Union member-states. It analyzes the key policy developments and initiatives in the field of education and culture at the beginning of the XXI century on part of the EU. Special attention is given to the objectives of arts education, its content, status, and models. The role of liberal education, arts in particular, in forming the competencies of young people for life in the twenty-first century has been widely recognized at the European level. The main objectives of arts education declared in national curricular, such as the development of students' artistic skills and knowledge, critical assessment of cultural heritage, promotion of self-expression, understanding of personal identity and cultural diversity by encouraging creativity, are similar among all the countries of the European Union. However, the «art for life» goal is mentioned only in some programs. Arts education in primary school fulfils its functions by enlarging knowledge and skills in the classroom through arts disciplines, mastering the technique and method of implementation of creative ideas that enrich younger students' possibilities for artistic expression and sensuality, meeting art works of different cultures and eras, practising creativity that allows children to realize their cultural and artistic projects. Contents of arts education in most EU countries include visual arts and music programs with crafts, dance, drama, architecture, and media arts being less popular at primary stage. In about half of the EU states minimal time for studying arts subjects is ranging from 50 to 100 hours per year at ISCED 1. Criteria for evaluating students' achievements in arts education are usually determined by teachers at the school level. They are based on the curriculum objectives or educational authorities' instructions. Primary school most commonly practises verbal comments. Today at primary school in the EU countries the following trends in arts education are observed: arts education is a compulsory component of basic education programs; fine arts and music are dominating other aesthetic disciplines (e.g., drama and dance) in programs for primary school; two models of arts education are being realized at ISCED 1 - combining arts disciplines as a distinct area within the curriculum or teaching them as separate subjects without any conceptual link between them; integration of arts education into the content of other disciplines (history, literature, languages, physical education, etc.); the content of school arts education is being enriched by the study of the media, including cinema, photography and digital arts, and encourages students and teachers to use ICT in the creative process; as a result of modern demographic changes the intercultural aspect is becoming one of the basic principles of teaching arts subjects; arts education is being practically oriented; the potential of arts education is used to create a situation of success in teaching underachieving students; schools are encouraged to organize extra-curricular arts activities and collaborate with professional artists and cultural institutions; local cultural features are more often considered. The above-mentioned processes impose new demands on teachers and schools, and need guidance and support at the political level.